Heat dissipation sheet

By using inorganic fillers with a specific particle size distribution in the thermal conductivity resin composition, a thermal dissipation sheet with thin thickness and excellent thermal conductivity is prepared, which solves the problem that thin thermal dissipation sheets in the prior art is difficult to maintain high thermal conductivity, and effectively dissipate heat in high-density electronic components.

JP7629012B2Active Publication Date: 2025-02-12DENKA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022530641
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-12
Filing Date
2021-06-11
Publication Date
2025-02-12
Estimated Expiration
2041-06-11

AI Technical Summary

Technical Problem

The prior art is difficult to produce thermal dissipation sheets that are both thin and have high thermal conductivity, especially in high-density thermal generation electronic components, and traditional methods are difficult to maintain a balance between high thermal conductivity and thin thickness.

Method used

By combining the first and second inorganic fillers with a specific particle size distribution in the thermally conductive resin composition, the particle size accumulation frequency and surface roughness thereof are controlled, and a thermal dissipation sheet with a thickness of 0.2 mm or thinner is prepared. The particle size distribution peak of the first inorganic filler is 15 μm or more, the particle size of the second inorganic filler is two-thirds or less of the particle size of the first inorganic filler, and the frequency accumulates at 50% or more.

Benefits of technology

A thermal dissipation sheet with a thickness of 0.2mm or thinner is achieved, with excellent thermal conductivity and surface roughness between 1.5 and 3.0μm, meeting the heat dissipation needs of high-density electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629012000002
    Figure 0007629012000002
  • Figure 0007629012000001
    Figure 0007629012000001
Patent Text Reader

Abstract

The present invention is a heat dissipation sheet that is formed by molding a thermally conductive resin composition that is formed by mixing a resin component and an inorganic filler component. The inorganic filler component includes a first inorganic filler and a second inorganic filler. The particle size distribution of the inorganic filler component has a first maximum M1 that originates from the first inorganic filler and a second maximum M2 that originates from the second inorganic filler, the particle diameter at the first maximum M1 being at least 15 μm, the particle diameter at the second maximum M2 being no more than 2 / 3 of the particle diameter at the first maximum M1, and the total of the frequencies between the start PS and end PE of the peak that includes the first maximum M1 being at least 50%. The surface roughness of the heat dissipation sheet is 1.5–3.0 μm, and the thickness is no more than 0.2 mm. The present invention makes it possible to provide a thin heat dissipation sheet that has excellent thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat dissipation sheet obtained by molding a thermally conductive resin composition. [Background technology]

[0002] For heat-generating electronic components such as power devices, transistors, thyristors, and CPUs, how to efficiently dissipate the heat generated during use is an important issue. Conventionally, the most common heat dissipation measures are (1) to make the insulating layer of the printed wiring board on which the heat-generating electronic components are mounted highly thermally conductive, and (2) to attach the heat-generating electronic components or the printed wiring board on which the heat-generating electronic components are mounted to a heat sink via electrically insulating thermal interface materials. Silicone resin or epoxy resin filled with ceramic powder is used as the insulating layer and thermal interface material for the printed wiring board.

[0003] In recent years, the heat density inside electronic devices has been increasing year by year due to the high speed and high integration of circuits in heat-generating electronic components and the increase in the mounting density of heat-generating electronic components on printed wiring boards. Therefore, there is a demand for ceramic powders with higher thermal conductivity than ever before (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 9-202663 Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, with the miniaturization of heat-generating electronic components, a thin heat dissipation sheet is required. Meanwhile, the doctor blade method is known as a method for continuously obtaining a thin molded body composed of ceramic raw material powder and organic components. The doctor blade method is a method for obtaining a molded body by thinly spreading a uniform slurry on a carrier film. The doctor blade method is widely used for ceramic substrates for electronic devices, ceramic packages for ICs, multilayer ceramic packages, multilayer ceramic circuit boards, ceramic capacitors, etc. From the viewpoint of mass production of thin heat dissipation sheets, it is desirable to produce thin heat dissipation sheets by the doctor blade method. In the doctor blade method, the slurry is flowed out from the gap between the blade and the carrier film to produce a sheet-like molded body. Then, the molded body can be made thin by reducing the dimension between the blade and the carrier film. However, with a slurry produced using the ceramic powder contained in a heat dissipation sheet having a conventional thickness, it was difficult to produce a thin heat dissipation sheet while maintaining a high level of thermal conductivity by reducing the dimension between the blade and the carrier film.

[0006] SUMMARY OF THE PRESENT EMBODIMENTS An object of the present invention is to provide a thin heat dissipation sheet having excellent thermal conductivity. [Means for solving the problem]

[0007] The inventors have conducted intensive research to achieve the above-mentioned object and have discovered that by using a combination of inorganic fillers of specific particle sizes and filling the inorganic fillers until the surface roughness falls within a specified range, a heat dissipation sheet can be obtained that exhibits good thermal conductivity while being 0.2 mm or less, or even 0.15 mm or less. The present invention is based on the above findings and has the following gist. [1] A heat dissipation sheet obtained by molding a thermally conductive resin composition obtained by blending an inorganic filler component and a resin component, the inorganic filler component including a first inorganic filler and a second inorganic filler, the particle size distribution of the inorganic filler component having a first maximum point attributable to the first inorganic filler and a second maximum point attributable to the second inorganic filler, the particle size at the first maximum point being 15 μm or more, the particle size at the second maximum point being two-thirds or less of the particle size at the first maximum point, the integrated value of the frequency from the peak start to the peak end at the peak having the first maximum point being 50% or more, the surface roughness being 1.5 to 3.0 μm, and the thickness being 0.2 mm or less. [2] The heat dissipation sheet according to the above [1], wherein, in the cumulative particle size distribution of the inorganic filler component, the cumulative frequency of particle sizes of 0 to 15 μm is less than 60%. [3] The heat dissipation sheet according to [1] or [2] above, further comprising a substrate having a thickness of 0.05 mm or less. Effect of the Invention

[0008] According to the present invention, a thin heat dissipation sheet having excellent thermal conductivity can be provided. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a diagram showing an example of the particle size distribution of an inorganic filler component. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The heat dissipation sheet of the present invention is produced by molding a thermally conductive resin composition comprising an inorganic filler component and a resin component.

[0011] [Thermal conductive resin composition] The thermally conductive resin composition of the present invention is obtained by blending an inorganic filler component and a resin component.

[0012] (Inorganic filler component) The inorganic filler component includes a first inorganic filler and a second inorganic filler, and the particle size distribution of the inorganic filler component has a first maximum point caused by the first inorganic filler and a second maximum point caused by the second inorganic filler. The particle size at the first maximum point is 15 μm or more, and the particle size at the second maximum point is two-thirds or less of the particle size at the first maximum point. The integrated frequency from the peak start to the peak end in the peak having the first maximum point is 50% or more.

[0013] The particle size distribution of the inorganic filler component in the thermally conductive resin composition can be measured, for example, as follows. Components other than the inorganic filler component of the thermally conductive resin composition are dissolved using a solvent such as toluene, xylene, or chlorinated hydrocarbon, and the components other than the inorganic filler component are removed from the thermally conductive composition. Then, the particle size distribution of the remaining inorganic filler component is measured using a laser diffraction scattering particle size distribution measuring device (LS-13 320) manufactured by Beckman Coulter, Inc. In addition, when there are three or more peaks, the peak with the highest frequency of maximum points is regarded as the peak having a maximum point due to the first inorganic filler, and the peak with the next highest frequency of maximum points is regarded as the peak having a maximum point due to the second inorganic filler. In this specification, the unit of frequency in the particle size distribution is volume %.

[0014] <The first inorganic filler> The first inorganic filler is not particularly limited as long as it is an inorganic filler having a higher thermal conductivity than the resin component. Examples of the first inorganic filler include alumina particles, aluminum nitride particles, and boron nitride particles. These first inorganic fillers can be used alone or in combination of two or more. Among these, the first inorganic filler is preferably boron nitride particles. When the first inorganic filler is boron nitride particles, the thermal conductivity of the heat dissipation sheet can be further increased. From the viewpoint of further increasing the thermal conductivity, chunky boron nitride particles are more preferable. The chunky boron nitride particles are formed by agglomeration of hexagonal boron nitride primary particles. Although the chunky boron nitride particles have the advantage of being able to further increase the thermal conductivity, they also have the disadvantage that the primary particles peel off, increasing the viscosity of the slurry of the thermally conductive resin composition, making it difficult to manufacture a thin heat dissipation sheet. From this viewpoint, the first inorganic filler is more preferably aggregated boron nitride particles formed by agglomeration of hexagonal boron nitride primary particles and having a crushing strength of 6 MPa or more. By using this, when preparing a slurry of the thermally conductive resin composition, it is possible to further suppress an increase in the viscosity of the slurry of the thermally conductive resin composition due to a part of the first inorganic filler peeling off from the first inorganic filler. Hereinafter, aggregated boron nitride particles having a crushing strength of 6 MPa or more will be simply referred to as aggregated boron nitride particles, and aggregated boron nitride particles having a crushing strength of less than 6 MPa will be referred to as aggregated boron nitride particles.

[0015] The particle size of the first maximum point due to the first inorganic filler is 15 μm or more. If the particle size of the first maximum point due to the first inorganic filler is less than 15 μm, the thermal conductive resin composition cannot contain the first inorganic filler at a high filling rate, and the thermal conductivity of the heat dissipation sheet produced using the thermal conductive resin composition may be reduced. From this viewpoint, the particle size of the first maximum point is preferably 20 μm or more, more preferably 30 μm or more, even more preferably 40 μm or more, and particularly preferably 50 μm or more. In addition, the particle size of the first maximum point is preferably 100 μm or less. If the particle size of the first maximum point is 100 μm or less, a thin heat dissipation sheet can be produced using the thermal conductive resin composition. From this viewpoint, the particle size of the first maximum point is more preferably 90 μm or less, and even more preferably 80 μm or less.

[0016] The first inorganic filler having the above particle size may be a commercially available product. When producing aggregate boron nitride particles for use as the first inorganic filler, the particle size of the first maximum point can be adjusted, for example, by adjusting the average particle size of B4C, which is the raw material of the aggregate boron nitride particles. That is, if the average particle size of B4C, which is the raw material of the aggregate boron nitride particles, is increased, the particle size of the first maximum point becomes large, and if the average particle size of B4C is decreased, the particle size of the first maximum point becomes small. In addition, the particle size of the first maximum point is caused by the first inorganic filler means that the maximum point of the particle size distribution of the first inorganic filler appears as the first maximum point in the particle size distribution of the inorganic filler component. In addition, due to the influence of the particle size distribution of inorganic filler components other than the first inorganic filler, the particle size of the first maximum point may be slightly different from the particle size of the maximum point of the particle size distribution of the first inorganic filler.

[0017] As described above, the first inorganic filler is preferably agglomerated boron nitride particles formed by agglomeration of hexagonal boron nitride primary particles and having a crushing strength of 6 MPa or more. If the crushing strength of the aggregate boron nitride particles is less than 6 MPa, when the thermally conductive resin composition is made into a slurry, some of the aggregate boron nitride particles may peel off from the aggregate boron nitride particles, the viscosity of the thermally conductive resin composition may increase, and a thin molded body may not be produced by the doctor blade method. In addition, the aggregate boron nitride particles may crumble due to stress applied to the aggregate boron nitride particles during kneading with the resin component or pressing the thermally conductive resin composition, and the thermal conductivity of the heat dissipation sheet may decrease. From this viewpoint, the crushing strength of the aggregate boron nitride particles is preferably 7 MPa or more, more preferably 8 MPa or more, even more preferably 9 MPa or more, even more preferably 10 MPa or more, and particularly preferably 11 MPa or more. The upper limit of the crushing strength of the aggregate boron nitride particles is not particularly limited, but is, for example, 30 MPa or less.

[0018] The crushing strength of the aggregated boron nitride particles and the aggregated boron nitride particles can be measured in accordance with JIS R1639-5:2007. Specifically, it can be measured as follows. Components other than the inorganic filler component of the thermally conductive resin composition are dissolved using a solvent such as toluene, xylene, or chlorinated hydrocarbon, and the components other than the inorganic filler component are removed from the thermally conductive resin composition. Then, the particle size distribution of the remaining inorganic filler component is measured using a laser diffraction scattering particle size distribution measuring device (LS-13 320) manufactured by Beckman Coulter, Inc. Next, the inorganic filler component is spread on the sample stage of a micro compression tester ("MCT-W500" manufactured by Shimadzu Corporation), and the diameters of the inorganic filler component in the X direction and the Y direction are measured, and the average is taken as the particle size of the inorganic filler component. Five inorganic filler components having a particle size within the range of the particle size of the first maximum point ±5 μm are selected, and a compression test is performed on each particle. The crushing strength (σ: MPa) is calculated from the dimensionless number (α = 2.48) that changes depending on the position within the particle, the crushing test force (P: N), and the particle size (d: μm), as follows: σ = α × P / (π × d 2) is used to calculate. The crushing strengths of five inorganic filler components are plotted in accordance with JIS R1625:2010, and the crushing strength at which the cumulative fracture rate is 63.2% is taken as the crushing strength of the first inorganic filler. The "cumulative fracture rate of 63.2%" is known as a value that satisfies lnln{1 / (1-F(t))}=0 in the Weibull distribution function, as taught in JIS R1625:2010 cited by the above JIS R1639-5:2007, and is a value based on the number of particles.

[0019] The cumulative amount of the frequency between the peak start and the peak end in the peak having the first maximum point is 50% or more. If the cumulative amount is less than 50%, the viscosity of the thermally conductive resin composition increases due to inorganic fillers other than the first inorganic filler, and a thin molded body cannot be produced by the doctor blade method. From this viewpoint, the cumulative amount is preferably 60% or more, more preferably 70% or more. In addition, in order to enable the inorganic filler component to exhibit the effect of containing a second inorganic filler described later, the cumulative amount is preferably 90% or less, more preferably 80% or less. In particular, by combining a large first inorganic filler having high strength with a second inorganic filler described later, the manufacturability can be improved and a heat dissipation sheet in which the inorganic filler is densely packed can be obtained. The cumulative amount of the frequency between the peak start and the peak end in the peak having the first maximum point is approximately the content (volume %) of the first inorganic filler in the inorganic filler component. Therefore, by analyzing the composition of the inorganic filler component, it is possible to identify the inorganic filler that corresponds to the first maximum point.

[0020] With reference to FIG. 1, the integrated amount of frequency between the peak start and the peak end in a peak having a first maximum point will be described. FIG. 1 is a diagram showing an example of the particle size distribution of an inorganic filler component. The horizontal axis is logarithmic. The symbol M1 indicates the first maximum point, and the symbol M2 indicates the second maximum point. PS indicates the peak start, and PE indicates the peak end. As shown in FIG. 1, when the bottoms of adjacent peaks overlap, the position of the valley of the peak becomes the peak start (PS). The integrated amount of the diagonal line part of the peak having the first maximum point (M1) becomes the integrated amount of frequency between the peak start (PS) and the peak end (PE) in the peak having the first maximum point (M1). When the bottoms of adjacent peaks overlap on the peak end side, the position of the valley of the peak becomes the peak end.

[0021] As described above, it is preferable to use aggregate boron nitride particles having high crushing strength as the first inorganic filler. Therefore, a method for producing the aggregate boron nitride particles having high crushing strength will be described. Agglomerated boron nitride particles, which are formed by agglomeration of hexagonal boron nitride primary particles and have a crushing strength of 6 MPa or more, can be produced, for example, by synthesizing boron carbide using boron and acetylene black as raw materials, and subjecting the obtained boron carbide to (1) a pressurized nitriding firing step and (2) a decarburization crystallization step. Each step will be described in detail below.

[0022] (1) Pressure nitriding firing process In the pressure nitriding and sintering step, boron carbide having an average particle size of 6 to 55 μm and a carbon content of 18 to 21% is pressure nitriding and sintered, thereby obtaining boron carbonitride suitable as a raw material for the aggregate boron nitride particles of the present invention.

[0023] (i) Boron carbide as raw material used in the pressure nitriding process Since the average particle size of the raw material boron carbide used in the pressure nitriding process strongly affects the final aggregate boron nitride particles, it is necessary to select one with an appropriate particle size, and it is preferable to use boron carbide with an average particle size of 6 to 55 μm as the raw material. In that case, it is preferable that the impurities of boric acid and free carbon are small.

[0024] The average particle size of the raw material boron carbide is preferably 6 μm or more, more preferably 7 μm or more, even more preferably 10 μm or more, and preferably 55 μm or less, more preferably 50 μm or less, and even more preferably 45 μm or less. The average particle size of the raw material boron carbide is preferably 7 to 50 μm, more preferably 10 to 45 μm. The average particle size of boron carbide can be measured using a laser diffraction scattering method particle size distribution analyzer (LS-13 320) manufactured by Beckman Coulter, Inc.

[0025] The carbon content of the raw material boron carbide used in the pressure nitriding process is desirably lower than the composition of B4C (21.7%), and it is desirable to use boron carbide with a carbon content of 18 to 21%. The reason for setting the carbon content of boron carbide in this range is that the smaller the amount of carbon released during the decarburization crystallization process described below, the denser the aggregate boron nitride particles will be produced, and also to reduce the carbon content of the final aggregate boron nitride particles. In addition, it is difficult to produce stable boron carbide with a carbon content of less than 18%, as the deviation from the theoretical composition becomes too large.

[0026] (ii) Pressure nitriding and firing The pressure nitriding sintering is carried out in an atmosphere with a specific sintering temperature and pressure conditions. The sintering temperature in the pressure nitriding sintering is preferably 1800 to 2200°C. The pressure in the pressure nitriding sintering is preferably 0.6 to 1.0 MPa. As the atmosphere in the pressure nitriding sintering, a gas in which the nitriding reaction proceeds is required, and examples thereof include nitrogen gas and ammonia gas, which can be used alone or in combination of two or more. Of these, nitrogen gas is suitable for nitriding and is cost-effective. The sintering time in the pressure nitriding sintering is preferably 6 to 30 hours.

[0027] (2) Decarburization crystallization process In the decarburization and crystallization process, the boron carbonitride obtained in the pressurized nitriding process is subjected to a heat treatment in which (a) it is placed in an atmosphere of atmospheric pressure or higher, (b) it is heated at a specific temperature, (c) it is heated to a sintering temperature in a specific temperature range, and (d) it is held at the sintering temperature for a certain period of time. This makes it possible to obtain aggregated boron nitride particles in which the primary particles (primary particles of hexagonal boron nitride in the form of scales) are aggregated into aggregates. In particular, if the conditions of the heat treatment are within the range described below, it is possible to make the crushing strength 6 MPa or more. In this decarburization and crystallization step, the boron carbonitride obtained from the prepared boron carbide as described above is decarburized and formed into flakes of a predetermined size, which are then aggregated to form aggregated boron nitride particles.

[0028] More specifically, in the decarburization crystallization process, 100 parts by mass of the boron carbonitride obtained in the pressure nitriding firing process is mixed with 65 to 130 parts by mass of at least one compound of boron oxide and boric acid to produce a mixture, and the resulting mixture is heated to a temperature at which decarburization can begin, and then heated at a heating rate of 5°C / min or less to a firing temperature of 1800°C or higher, and a heat treatment is performed in which the temperature is maintained at the firing temperature for more than 0.5 hours and less than 40 hours.

[0029] The pressure condition of "(a) atmosphere of normal pressure or higher" in the decarburization and crystallization process is preferably normal pressure or higher, more preferably 0.1 MPa or higher. The upper limit of the pressure condition of the atmosphere is not particularly limited, but is preferably 1 MPa or lower. The "atmosphere" in the decarburization and crystallization process is preferably nitrogen gas. The temperature rise to the "(b) specific temperature rise" in the decarburization crystallization step may be either one-stage or multi-stage. The "temperature at which decarburization can start" is not particularly limited and may be any temperature that is normally used, for example, about 800 to 1200°C (preferably about 1000°C). The "first stage of temperature rise" may be performed, for example, in the range of 5 to 20°C / min, and preferably 8 to 12°C / min. The specific temperature range (the firing temperature after heating) in "(c) heating to a firing temperature within the specific temperature range" is 1800°C or higher, and may be more preferably 2000°C or higher. The upper limit of the holding temperature is not particularly limited, but is preferably 2200°C or lower, and more preferably 2100°C or lower. If the holding temperature is too low, below 1800°C, grain growth may not occur sufficiently, and the thermal conductivity may decrease. On the other hand, if the holding temperature is 1800°C or higher, grain growth is likely to occur well, and the thermal conductivity may be easily improved. The period of time (calcination time after temperature rise) of "(d) holding at calcination temperature for a certain period of time" is not particularly limited as long as crystallization proceeds sufficiently, and in a preferred embodiment, it can be, for example, in the range of more than 0.5 hours and less than 40 hours, more preferably in the range of 1 to 30 hours. The holding time may be preferably 1 hour or more, more preferably 3 hours or more, even more preferably 5 hours or more, and even more preferably 10 hours or more. The upper limit of the holding time may be preferably 30 hours or less, more preferably 20 hours or less. When the holding time is 1 hour or more, it is expected that grain growth will occur well, and when the holding time is 30 hours or less, it is expected that the grain growth will proceed too much and the particle strength will be reduced, and it is also expected that the disadvantage of a long calcination time will be reduced industrially.

[0030] The aggregate boron nitride particles of the present invention can be obtained through the above-mentioned pressurized nitriding firing step and the above-mentioned decarburization crystallization step. Furthermore, when loosening weak agglomerations between aggregate boron nitride particles, it is preferable to pulverize or disintegrate the aggregate boron nitride particles obtained in the decarburization crystallization step, and further classify them. The pulverization and disintegration are not particularly limited, and a commonly used pulverizer and disintegrator may be used, and the classification may be performed using a general sieving method that results in an average particle size of 20 μm or more. For example, a method of performing disintegration using a Henschel mixer or a mortar, followed by classification using a vibrating sieve, may be mentioned.

[0031] <Second inorganic filler> The particle size of the second maximum point caused by the second inorganic filler is 2 / 3 or less of the particle size of the first maximum point. If the particle size of the second maximum point is larger than 2 / 3 of the particle size of the first maximum point, the thermally conductive resin composition cannot contain the inorganic filler component at a high filling rate, and a thin heat dissipation sheet having excellent thermal conductivity may not be produced. From this viewpoint, the particle size of the second maximum point is preferably 60% or less of the particle size of the first maximum point, more preferably 55% or less of the particle size of the first maximum point, and even more preferably 52% or less of the particle size of the first maximum point. The lower limit of the particle size of the second maximum point is, for example, 20% or more of the particle size of the first maximum point, and preferably 30% or more or 40% or more. The second maximum point can be measured in the same manner as the first maximum point. There may be a plurality of second maximum points. In addition, the integrated amount of the frequency between the peak start and the peak end in the peak having the second maximum point is approximately the content (volume %) of the second inorganic filler in the inorganic component. Therefore, by analyzing the composition of the inorganic filler component, it is possible to identify the inorganic filler that corresponds to the second maximum point. The integrated amount of the frequency between the peak start and the peak end in the peak having the second maximum point is 50% or less, may be 45% or less, may be 40% or less, or may be 35% or less, and the lower limit may be 10% or more, may be 15% or more, may be 20% or more, or may be 25% or more.

[0032] The second inorganic filler is not particularly limited as long as it is an inorganic filler having a higher thermal conductivity than the resin component. Examples of the second inorganic filler include alumina particles, aluminum nitride particles, and boron nitride particles. These second inorganic fillers can be used alone or in combination of two or more. Among these, the second inorganic filler is preferably boron nitride particles. When the second inorganic filler is boron nitride particles, the thermal conductivity of the heat dissipation sheet produced using the thermal conductive resin composition can be further increased. From the viewpoint of further increasing the thermal conductivity, chunky boron nitride particles are more preferable. The chunky boron nitride is formed by agglomerating hexagonal boron nitride primary particles. Although the chunky boron nitride particles have the advantage of further increasing the thermal conductivity, they also have the disadvantage that the primary particles peel off, making them difficult to manufacture. From this viewpoint, the second inorganic filler is more preferably agglomerated boron nitride particles formed by agglomerating hexagonal boron nitride primary particles and having a crushing strength of 6 MPa or more. Hereinafter, for the second inorganic filler, the aggregate boron nitride particles having a crushing strength of 6 MPa or more will be simply referred to as aggregate boron nitride particles, and the aggregate boron nitride particles having a crushing strength of less than 6 MPa will be referred to as aggregated boron nitride particles. The aggregate boron nitride particles of the second inorganic filler can be produced in the same manner as the aggregate boron nitride particles of the first inorganic filler. In addition, by adjusting the average particle size of B4C, which is the raw material of the aggregate boron nitride particles, the particle size of the second maximum point caused by the second inorganic filler can be made two-thirds or less of the particle size of the first maximum point.

[0033] As for the second inorganic filler, the crushing strength of the aggregated boron nitride particles and the aggregated boron nitride particles can be measured in accordance with JIS R1639-5:2007. Specifically, it can be measured as follows. Components other than the inorganic filler component of the thermally conductive resin composition are dissolved using a solvent such as toluene, xylene, or chlorinated hydrocarbon, and the components other than the inorganic filler component are removed from the thermally conductive resin composition. Then, the particle size distribution of the remaining inorganic filler component is measured using a laser diffraction scattering particle size distribution measuring device (LS-13 320) manufactured by Beckman Coulter, Inc. Next, the inorganic filler component is spread on the sample stage of a micro compression tester ("MCT-W500" manufactured by Shimadzu Corporation), and the diameters of the inorganic filler component in the X direction and the Y direction are measured, and the average is taken as the particle size of the inorganic filler component. Five inorganic filler components having a particle size within the range of the particle size of the second maximum point ±5 μm are selected, and a compression test is performed on each particle. The crushing strength (σ: MPa) is calculated from the dimensionless number (α = 2.48) that changes depending on the position within the particle, the crushing test force (P: N), and the particle size (d: μm), as follows: σ = α × P / (π × d 2 The crushing strength of the five inorganic filler components is plotted in accordance with JIS R1625:2010, and the crushing strength at which the cumulative fracture rate is 63.2% is defined as the crushing strength of the second inorganic filler.

[0034] In the particle size accumulation of the inorganic filler component, the cumulative frequency of particle sizes of 0 to 15 μm is preferably less than 60%. In this case, the content of inorganic filler having a particle size of 15 μm or more in the inorganic filler component is approximately 40% by volume or more, the thermal conductive resin composition can contain the inorganic filler component in a high filling ratio, and the thermal conductivity of the heat dissipation sheet produced using the thermal conductive resin composition can be further increased. From this viewpoint, in the particle size accumulation of the inorganic filler component, the cumulative frequency of particle sizes of 0 to 15 μm is more preferably less than 50%, even more preferably less than 40%, and even more preferably less than 30%.

[0035] (Resin component) Examples of the resin component include epoxy resin, silicone resin (including silicone rubber), acrylic resin, phenolic resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyamide (e.g., polyimide, polyamideimide, polyetherimide, etc.), polyester (e.g., polybutylene terephthalate, polyethylene terephthalate, etc.), polyphenylene ether, polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide-modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin, etc. Among these, silicone resin is preferred from the viewpoint of heat resistance, flexibility, and adhesion to heat sinks, etc. Silicone resin is preferably vulcanized and cured by organic peroxide. The viscosity of the thermally conductive resin composition at 25°C is, for example, 100,000 cp or more from the viewpoint of improving the flexibility of the sheet-shaped molded body.

[0036] The content of the inorganic filler component in the total of 100% by volume of the inorganic filler component and the resin component is preferably 30 to 85% by volume, more preferably 40 to 80% by volume. When the content of the inorganic filler component is 30% by volume or more, the thermal conductivity is improved and sufficient heat dissipation performance is easily obtained. When the content of the inorganic filler component is 85% by volume or less, it is possible to reduce the tendency for voids to be generated during molding, and to reduce the deterioration of insulation and mechanical strength. In addition, the content of the resin component in 100% by volume of the thermally conductive resin composition is preferably 15 to 70% by volume, more preferably 20 to 60% by volume.

[0037] (solvent) In order to adjust the viscosity of the thermally conductive resin composition, the thermally conductive resin composition may further contain a solvent. The solvent is not particularly limited as long as it can dissolve the resin component and can be easily removed from the thermally conductive resin composition after the thermally conductive resin composition is applied. When the resin component is a silicone resin, examples of the solvent include toluene, xylene, and chlorine-based hydrocarbons. Among these solvents, toluene is preferred from the viewpoint of ease of removal. The content of the solvent can be appropriately selected according to the target viscosity of the thermally conductive resin composition. The content of the solvent is, for example, 40 to 200 parts by mass with respect to 100 parts by mass of the components other than the solvent of the thermally conductive resin composition.

[0038] The thermally conductive resin composition may contain components other than the inorganic filler component, the resin component, and the solvent. The other components are additives, impurities, etc., and the content of the other components is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 1 part by mass or less, relative to 100 parts by mass of the total of the inorganic filler component and the resin component.

[0039] [Heat dissipation sheet] As described above, the heat dissipation sheet of the present invention is formed by molding the above-mentioned thermally conductive resin composition. By using the heat conductive resin composition of the present invention, a thin heat dissipation sheet can be easily produced by the doctor blade method. The thickness of the heat dissipation sheet of the present invention is 0.20 mm or less. If the thickness of the heat dissipation sheet is 0.20 mm or less, it is possible to meet the requirement for the thickness of the heat dissipation sheet associated with the miniaturization of heat-generating electronic components. From this viewpoint, the thickness of the heat dissipation sheet is more preferably 0.15 mm or less, even more preferably 0.12 mm or less, and even more preferably 0.10 mm or less.

[0040] The surface roughness of the heat dissipation sheet of the present invention is 1.5 to 3.0 μm. By employing a combination of the first inorganic filler and the second inorganic filler, the inorganic filler component is sufficiently filled until the surface roughness is 1.5 μm or more, and the heat dissipation sheet can be made thin while achieving sufficient thermal conductivity. This is presumably because the use of a specific combination of inorganic fillers allows the amount of filling to be increased, and also results in a filling form that is easy to transfer heat. If the surface roughness of the heat dissipation sheet is less than 1.5 μm, the thermal conductivity may be reduced. This is considered to be because the ratio of the inorganic filler component in the thermally conductive resin composition is low, or the above-mentioned special filling form is not formed. Note that, if the ratio of the inorganic filler component in the thermally conductive resin composition is low, the inorganic filler component is buried in the resin component, and the surface of the heat dissipation sheet becomes very smooth. On the other hand, if the surface roughness of the heat dissipation sheet is greater than 3.0 μm, the thermal conductivity may be reduced. It is considered that the inorganic filler component is not in a sufficiently densely packed state, the filling rate is not increased, and the above-mentioned filling form is not reached, and the thermal conductivity is not increased. The surface roughness of the heat dissipation sheet is the arithmetic mean roughness Ra, which is measured in accordance with the description in JIS B 0601:2013 "Geometric characteristics of products (GPS) - Surface quality: Profile curve method - Terms, definitions and surface quality parameters."

[0041] The heat dissipation sheet preferably includes a substrate having a thickness of 0.05 mm or less. This allows the heat dissipation sheet to be made thin, and the heat dissipation sheet can be prevented from being damaged during handling. The substrate is not particularly limited as long as it can hold the thermally conductive resin composition layer, has a moderate strength, is 0.05 mm or less in thickness, and has flexibility. Examples of the substrate include paper, cloth, film, nonwoven fabric, and metal foil. Among these, cloth is preferred from the viewpoint of having good adhesion to the thermally conductive resin composition layer and being able to suppress the inhibition of thermal conduction of the thermally conductive resin composition by the substrate by providing an opening portion, and glass cloth and polyamide-imide fiber cloth are more preferred from the viewpoint of being able to maintain the strength of the substrate to a certain extent even if the substrate is made thin and the opening is made large, and glass cloth is even more preferred. In addition, from the viewpoint of being able to make the heat dissipation sheet thin, the thickness of the substrate is more preferably 0.03 mm or less. In addition, from the viewpoint of the strength of the substrate, the thickness of the substrate is preferably 0.005 mm or more. When the substrate is a glass cloth, the glass cloth may be subjected to a silane coupling treatment in order to prevent gaps from being formed between the thermally conductive resin composition and the glass cloth.

[0042] The heat dissipation sheet can be produced by the doctor blade method. For example, the heat dissipation sheet can be produced as follows. Raw materials other than the solvent, such as inorganic filler components and resin components, are dispersed in a solvent to produce a slurry-like thermally conductive resin composition. Hereinafter, the slurry-like thermally conductive resin composition may be simply referred to as "slurry". Since the aggregate boron nitride particles used as the first inorganic filler have a high crushing strength of 6 MPa, when raw materials other than the solvent are dispersed in the solvent, the hexagonal boron nitride primary particles are hardly peeled off from the aggregate boron nitride particles. This makes it possible to suppress an increase in the viscosity of the slurry when raw materials other than the solvent of the thermally conductive resin composition are dispersed in the solvent. The viscosity of the slurry can also be reduced by increasing the amount of solvent. However, in this case, when the thermally conductive resin composition is molded into a sheet, the thermally conductive resin composition may foam, or when the solvent is removed from the sheet-shaped molded body, additives such as vulcanizing agents and curing agents in the thermally conductive composition may become ineffective, so it is desirable to reduce the viscosity of the slurry without increasing the amount of solvent. In addition, since the average particle size of the block boron nitride particles used as the first inorganic filler is relatively large, approximately 15 μm or more, after the raw materials other than the solvent of the thermally conductive resin composition are dispersed in the solvent, the dispersed inorganic filler components can be prevented from agglomerating to make the slurry non-uniform. Note that if the average particle size of the inorganic filler is very small, the dispersed inorganic filler may agglomerate to make the slurry non-uniform.

[0043] The prepared slurry is supplied to a doctor blade device. The doctor blade device causes the slurry to flow out from the gap between the blade and the carrier film, and forms the thermally conductive resin composition into a sheet. The thickness of the molded product can be precisely controlled by adjusting the dimension between the blade and the carrier film and the moving speed of the carrier film. In addition, a doctor blade device having two blades may be used to more precisely control the pressure of the slurry and more precisely control the thickness of the molded product.

[0044] The slurry that flows out from the gap between the blade and the carrier film moves through the doctor blade device together with the carrier film, and dries and solidifies during the movement to become a sheet-like molded body. The obtained sheet-like molded body is, for example, pressurized and heated to harden it into a heat dissipation sheet. In addition, a release agent may be applied to the surface of the carrier film to make it easy to peel the heat dissipation sheet from the carrier film. Examples of the release agent include silicone-based release agents, alkyl pendant-based release agents, and condensation wax-based release agents.

[0045] When the heat dissipation sheet includes a substrate, for example, the heat dissipation sheet is produced as follows. The substrate is sandwiched between two sheet-like molded bodies with carrier films obtained by the doctor blade method to obtain a laminate. The layer structure of the laminate at this time is carrier film / thermal conductive resin composition / substrate / thermal conductive resin composition / carrier film. The laminate is then pressurized and heated, and the carrier film is peeled off to obtain a heat dissipation sheet. In this case, a release agent may be applied to the surface of the carrier film so that the heat dissipation sheet can be easily peeled off from the carrier film.

[0046] The heat dissipation sheet can also be produced by calendar processing. However, when the sheet-shaped thermally conductive resin composition passes through the calendar roll, there is a risk that some of the aggregate boron nitride particles in the thermally conductive resin composition may peel off. Therefore, it is preferable to produce the heat dissipation sheet by the doctor blade method. EXAMPLES

[0047] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0048] The thermally conductive resin compositions of the Examples and Comparative Examples were evaluated as follows. (Slurry Viscosity) The viscosity of the slurry used in producing the heat dissipation sheets of the Examples and Comparative Examples was measured using a Brookfield viscometer at a rotation speed of 20 rpm after leaving the slurry to stand for 30 seconds.

[0049] (particle size distribution) Components other than the inorganic filler component of the thermally conductive resin composition were dissolved using toluene, and components other than the inorganic filler component were removed from the thermally conductive resin composition. The particle size distribution of the remaining inorganic filler component was measured using a laser diffraction scattering particle size distribution measuring device (LS-13 320) manufactured by Beckman Coulter, Inc. Then, from the obtained particle size distribution, the first maximum value and the second maximum value, as well as the integrated amount of frequency from the peak start to the peak end in the peak having the first maximum point were obtained.

[0050] (Crushing strength) The crushing strength of the aggregated boron nitride particles and the aggregated boron nitride particles was measured in accordance with JIS R1639-5:2007. Specifically, the components other than the inorganic filler component of the thermally conductive resin composition were dissolved using a solvent such as toluene, xylene, or chlorinated hydrocarbon, and the components other than the inorganic filler component were removed from the thermally conductive resin composition. The particle size distribution of the remaining inorganic filler component was then measured using a laser diffraction scattering particle size distribution measuring device (LS-13 320) manufactured by Beckman Coulter, Inc. Next, the inorganic filler component was spread on the sample stage of a microcompression tester ("MCT-W500" manufactured by Shimadzu Corporation), and the diameters of the inorganic filler component in the X and Y directions were measured, and the average was taken as the particle size of the inorganic filler component. Five inorganic filler components having a particle size within the range of the particle size at the first maximum point ±5 μm were selected, and a compression test was performed on each particle. The crushing strength (σ: MPa) is calculated from the dimensionless number (α = 2.48) that changes depending on the position within the particle, the crushing test force (P: N), and the particle size (d: μm), as follows: σ = α × P / (π × d 2 ) was used to calculate. The crushing strengths of the five inorganic filler components were plotted in accordance with JIS R1625:2010, and the crushing strength at which the cumulative fracture rate was 63.2% was determined as the crushing strength of the first inorganic filler. The crushing strength of the second inorganic filler was also measured in the same manner.

[0051] (Cumulative amount of frequency of particle sizes between 0 and 15 μm) Components other than the inorganic filler component of the thermally conductive resin composition were dissolved using toluene, and components other than the inorganic filler component were removed from the heat dissipation sheet. The particle size accumulation of the remaining inorganic filler components was then measured using a laser diffraction scattering particle size distribution measuring device (LS-13 320) manufactured by Beckman Coulter, Inc. The accumulated amount of the frequency of particle sizes of 0 to 15 μm was then calculated from the obtained particle size accumulation.

[0052] The heat dissipation sheets of the examples and comparative examples were evaluated as follows. (thermal resistance) The thermal resistance of the heat dissipation sheet was measured by applying a load of 1 MPa in accordance with ASTM D5470.

[0053] (Relative Density) The relative density was calculated by dividing the density of the heat dissipation sheet by the theoretical density using the Archimedes method.

[0054] (Surface roughness Ra) The surface roughness of the heat dissipation sheet is the arithmetic mean roughness Ra, which was measured in accordance with JIS B 0601:2013.

[0055] Example 1 In Example 1, chunky boron nitride particles were produced by the following steps: synthesis of boron carbide, pressure nitridation process, and decarburization crystallization process.

[0056] (Boron carbide synthesis) 100 parts by mass of orthoboric acid (hereinafter referred to as boric acid) manufactured by Nippon Denko Co., Ltd. and 35 parts by mass of acetylene black (HS100) manufactured by Denka Co., Ltd. were mixed using a Henschel mixer, then filled into a graphite crucible and heated in an arc furnace in an argon atmosphere at 2200°C for 5 hours to synthesize boron carbide (B4C). The synthesized boron carbide block was pulverized in a ball mill for 1 hour, sieved using a sieve to a particle size of 75 μm or less, and further washed with an aqueous nitric acid solution to remove impurities such as iron, and then filtered and dried to produce boron carbide powder with an average particle size of 20 μm. The carbon content of the obtained boron carbide powder was 20.0%.

[0057] (Pressure nitriding process) The synthesized boron carbide was loaded into a boron nitride crucible and then heated in a resistance heating furnace at 2000°C and 9 atm (0.8 MPa) for 10 hours in a nitrogen gas atmosphere to obtain boron carbonitride (B4CN4).

[0058] (Decarburization crystallization process) 100 parts by mass of the synthesized boron carbonitride and 90 parts by mass of boric acid were mixed using a Henschel mixer, and then filled into a boron nitride crucible. Using a resistance heating furnace, the mixture was heated in a nitrogen gas atmosphere under a pressure condition of 0.2 MPa, at a heating rate of 10 ° C. / min from room temperature to 1000 ° C. and a heating rate of 2 ° C. / min from 1000 ° C., and heated at a firing temperature of 2020 ° C. for a holding time of 10 hours to synthesize aggregated boron nitride particles in which primary particles were aggregated into aggregates. The synthesized aggregated boron nitride particles were decomposed and crushed using a Henschel mixer, and then classified using a nylon sieve with a mesh size of 150 μm using a sieve net. By crushing and classifying the fired product, aggregated boron nitride particles 1 in which primary particles were aggregated into aggregates were obtained.

[0059] The average particle size (D50) of the obtained aggregate boron nitride particles 1 measured by a laser scattering method was 40 μm. The aggregate boron nitride particles 1 also had a crushing strength of 12 MPa.

[0060] (Making heat dissipation sheets) The total volume of the obtained aggregated boron nitride particles 1, aggregated boron nitride particles (manufactured by Denka Co., Ltd., product name "SGPS", average particle size: 20 μm, crushing strength: 1.5 MPa), scaly boron nitride particles (manufactured by Denka Co., Ltd., product name "SP-3-7", average particle size: 3 μm) and liquid silicone resin 1 (methylvinylpolysiloxane, manufactured by Dow-Toray Co., Ltd., product name "CF-3110") was 100%, and 45% by volume of aggregated boron nitride particles 1, 12% by volume of aggregated boron nitride particles, 3% by volume of The scaly boron nitride particles and 40% by volume of silicone resin 1, 1 part by mass of a curing agent (2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, manufactured by Kayaku Nouryon Co., Ltd., trade name "Trigonox 101") per 100 parts by mass of silicone resin, 0.5% by mass of a silane coupling agent (dimethyldimethoxysilane, manufactured by Dow Toray Co., Ltd., trade name "DOWSIL Z-6329 Silane", viscosity at 25°C: 1 cp) per 100 parts by mass of the total of the block boron nitride particles, agglomerated boron nitride particles and scaly boron nitride particles, 15 parts by mass of water per 100 parts by mass of the silane coupling agent, and 110 parts by mass of toluene per 100 parts by mass of the total of the above raw materials were charged into a stirrer (manufactured by HEIDON, trade name "Three One Motor") and mixed for 15 hours using a turbine-type stirring blade to prepare a slurry of a thermally conductive resin composition. The viscosity of the slurry was 10,000 cp. The above slurry was then coated to a thickness of 0.2 mm on a PET film (carrier film) having a thickness of 0.05 mm by a doctor blade method, and dried at 75°C for 5 minutes to produce a sheet-like molded product with a PET film. A laminate was produced by sandwiching a glass cloth (thickness: 0.025 mm) between the sheet-like molded products with a PET film so that the coated surfaces of the thermally conductive resin composition were in contact with both sides of the glass cloth. The layer structure of the laminate was PET film / thermally conductive resin composition / glass cloth / thermally conductive resin composition / PET film. The obtained laminate was then heated at a temperature of 150°C and a pressure of 160 kg / cm. 2 The PET films on both sides were peeled off to obtain a sheet having a thickness of 0.09 mm. The sheet was then subjected to secondary heating at normal pressure and 150° C. for 4 hours to obtain the heat dissipation sheet of Example 1.

[0061] Example 2 A heat dissipation sheet of Example 2 was produced in the same manner as in Example 1, except that the amount of toluene was changed from 110 parts by mass to 60 parts by mass, and the coating conditions of the doctor blade method were changed to produce a heat dissipation sheet with a thickness of 0.20 mm. The viscosity of the slurry was 7000 cp.

[0062] Example 3 The heat dissipation sheet of Example 3 was produced in the same manner as Example 1, except that instead of 45 volume% of aggregate boron nitride particles 1 having an average particle diameter of 40 μm and a crushing strength of 12 MPa, 42 volume% of aggregate boron nitride particles 2 having an average particle diameter of 75 μm and a crushing strength of 12 MPa was used, instead of 12 volume% of agglomerated boron nitride particles, 11 volume% of aggregate boron nitride particles 3 having an average particle diameter of 38 μm and a crushing strength of 12 MPa was used, no flake boron nitride particles were used, the amount of silicone resin 1 was changed from 40 volume% to 47 volume%, the amount of toluene was changed from 110 parts by mass to 100 parts by mass, and the coating conditions for the doctor blade method were changed to produce a heat dissipation sheet with a thickness of 0.10 mm. The aggregate boron nitride particles 2 and 3 used in the heat dissipation sheet of Example 3 were produced in the same manner as the aggregate boron nitride particles 1 used in the heat dissipation sheet of Example 1, except that the average particle size of the boron carbide powder was changed by changing the grinding time of the synthesized boron carbide aggregates in a ball mill. The viscosity of the slurry was 10,000 cp.

[0063] Example 4 A heat-dissipating sheet of Example 4 was produced in the same manner as in Example 3, except that the coating conditions of the doctor blade method were changed to produce a heat-dissipating sheet with a thickness of 0.20 mm.

[0064] Example 5 Except for the fact that chunky boron nitride particles 4 having an average particle size of 55 μm and a crushing strength of 10 MPa were used instead of chunky boron nitride particles 2, and the coating conditions of the doctor blade method were changed to produce a heat dissipation sheet with a thickness of 0.10 mm, Example 3The heat dissipation sheet of Example 5 was produced in the same manner as in Example 1. The aggregate boron nitride particles 4 used in the heat dissipation sheet of Example 5 were produced in the same manner as the aggregate boron nitride particles 1 used in the heat dissipation sheet of Example 1, except that the average particle size of the boron carbide powder was changed by changing the grinding time of the synthesized boron carbide aggregates in a ball mill. The viscosity of the slurry was 9500 cp.

[0065] Example 6 A heat-dissipating sheet of Example 6 was produced in the same manner as in Example 5, except that the coating conditions of the doctor blade method were changed to produce a heat-dissipating sheet with a thickness of 0.20 mm.

[0066] Comparative Example 1 The heat dissipation sheet of Comparative Example 1 was produced in the same manner as in Example 1, except that the lump boron nitride particles 1 and the scaly boron nitride particles were not mixed, the amount of aggregated boron nitride particles was changed from 12% by volume to 60% by volume, the amount of silane coupling agent was changed from 0.5 parts by mass to 0.2 parts by mass, and the coating conditions of the doctor blade method were changed to produce a heat dissipation sheet with a thickness of 0.20 mm. The viscosity of the slurry was 12000 cp. In addition, because the viscosity of the slurry was high, it was not possible to produce a heat dissipation sheet with a thickness of 0.15 mm or less.

[0067] Comparative Example 2 A heat-dissipating sheet of Comparative Example 2 was produced in the same manner as Comparative Example 1, except that the coating conditions of the doctor blade method were changed to produce a heat-dissipating sheet with a thickness of 0.30 mm.

[0068] Comparative Example 3 A slurry was prepared in the same manner as in Example 5, except that aggregate boron nitride particles 3 were replaced with aggregate boron nitride particles 1. However, because the viscosity of the slurry was high at 16,000 cp, it was not possible to prepare a heat dissipation sheet having a thickness of 0.20 mm.

[0069] Comparative Example 4 A slurry was prepared in the same manner as in Example 1, except that the blending amount of the chunky boron nitride particles 1 was changed from 45 volume % to 12 volume %, and the blending amount of the agglomerated boron nitride particles was changed from 12 volume % to 45 volume %. However, because the viscosity of the slurry was high at 18000 cp, it was not possible to prepare a heat dissipation sheet having a thickness of 0.20 mm.

[0070] The evaluation results of the heat dissipation sheets of Examples 1 to 6 and Comparative Examples 1 to 4 are shown in Table 1. [Table 1]

[0071] From the evaluation results of the heat dissipation sheets of Examples 1 to 6, it was found that a thin heat dissipation sheet with excellent thermal conductivity can be obtained when the particle size distribution of the inorganic filler component in the heat dissipation sheet has a first maximum point due to a first inorganic filler and a second maximum point due to a second inorganic filler, the particle size of the first maximum point is 15 μm or more, the particle size of the second maximum point is two-thirds or less of the particle size of the first maximum point, the integrated frequency from the peak start to the peak end in a peak having the first maximum point is 50% or more, the surface roughness of the heat dissipation sheet is 1.5 to 3.0 μm, and the thickness of the heat dissipation sheet is 0.2 mm or less. From the evaluation results of the heat dissipation sheets of Comparative Examples 1 and 2, it was found that the thermal conductivity characteristics deteriorated without the second inorganic filler. It was also found that a thin heat dissipation sheet of 0.15 mm or less could not be produced without the second inorganic filler. For Comparative Example 3, a heat dissipation sheet could not be produced, but due to the composition of the thermally conductive resin composition, it is believed that the particle size at the second maximum point was larger than two-thirds of the particle size at the first maximum point. For Comparative Example 4, a heat dissipation sheet could not be produced, but due to the composition of the thermally conductive resin composition, it is considered that the integrated frequency from the peak start to the peak end at the peak having the first maximum point was less than 50%.

[0072] Example 7 A 0.2 mm heat dissipation sheet was produced in the same manner as in Example 4, except that the silicone resin CF3110 was changed to an epoxy resin (bisphenol type epoxy resin manufactured by Mitsubishi Chemical Corporation, model number: JER-807), the curing agent Trigonox 101 (1 part by mass) was changed to a curing agent MEH-8005 (manufactured by Meiwa Kasei Co., Ltd., 10 parts by mass), and 2PHZ-PW (manufactured by Shikoku Kasei Corporation, 1 part by mass) was added as a curing accelerator, and the thermal resistance was measured by the method described above. The surface roughness was 2.6 μm.

[0073] Comparative Example 5 A 0.2 mm heat dissipation sheet was produced in the same manner as in Comparative Example 1, except that the silicone resin CF3110 was changed to an epoxy resin (bisphenol type epoxy resin manufactured by Mitsubishi Chemical Corporation, model number: JER-807), the curing agent Trigonox 101 (1 part by mass) was changed to a curing agent MEH-8005 (manufactured by Meiwa Kasei Co., Ltd., 10 parts by mass), and 2PHZ-PW (manufactured by Shikoku Kasei Corporation, 1 part by mass) was added as a curing accelerator, and the thermal resistance was measured by the method described above. The surface roughness was 3.2 μm.

[0074] Comparing the thermal resistance of Example 7 with that of Comparative Example 5, Example 7 had a lower thermal resistance and was a better result. Therefore, the effect obtained by combining a specific inorganic filler was obtained regardless of the type of resin.

Claims

1. A heat dissipation sheet obtained by molding a thermally conductive resin composition containing an inorganic filler component and a resin component, the inorganic filler component includes a first inorganic filler and a second inorganic filler; the particle size distribution of the inorganic filler component has a first maximum point attributable to the first inorganic filler and a second maximum point attributable to the second inorganic filler; the particle size at the first maximum point is 40 μm or more, and the particle size at the second maximum point is two-thirds or less of the particle size at the first maximum point; an integrated amount of frequency from a peak start to a peak end in the peak having the first maximum point is 75% or more; The surface roughness is 1.5 to 3.0 μm. A heat dissipation sheet having a thickness of 0.2 mm or less.

2. 2. The heat dissipation sheet according to claim 1, wherein the cumulative particle size of the inorganic filler component is such that the cumulative frequency of particle sizes of 0 to 15 μm is less than 60%.

3. The heat dissipation sheet according to claim 1 or 2, further comprising a substrate having a thickness of 0.05 mm or less.

Citation Information

Patent Citations

  • Melamine borate particle, its production and use thereof and production of hexagonal boron nitride powder

    JP1997202663A

  • Inorganic powder and its application

    JP2005343983A

  • Thermally conductive sheet, and thermally conductive sheet with release sheet

    JP2015021025A

  • Heat-radiating sheet and device having heat-radiating sheet

    WO2019065150A1